A Distinct Metabolite Profile Correlates with Neurodegenerative Conditions and the Severity of Congenital Hydrocephalus - Garcia-Bonilla, María; Garcia-Leon, Maria L; Muñoz-Hernandez, M Carmen; Domínguez-Pinos, Dolores; Martínez-León, María Isabel; Peñalver, Ana; Castilla, Ana; Alonso, Francisco J; Marquez, Javier; Shumilov, Kirill; Hidalgo-Sanchez, Ramon; Gutiérrez-Pérez, Antonia; et al. (Oxford Academic, 2018)
In congenital hydrocephalus, cerebrospinal fluid accumulation is associated with increased intracranial pressure (ICP), ischemia/hypoxia, metabolic impairment, neuronal damage, and astrocytic reaction. The aim of this study was to identify whether a metabolite profile revealing tissue responses according to the severity of hydrocephalus can be detected. The hyh mutant mouse used for this study exhibits 2 different forms of hydrocephalus, severe and moderate. In a comprehensive investigation into the 2 progressions of hydrocephalus, mice with severe hydrocephalus were found to have higher ICP and astrocytic reaction. Several metabolites from the mouse brain cortex were analyzed with 1H high-resolution magic angle spinning nuclear magnetic resonance (1H HR-MAS NMR) spectroscopy. A differential profile for metabolites including glutamate and glutamine was found to correlate with the severity of hydrocephalus and can be explained due to differential astrocytic reactions, neurodegenerative conditions, and the presence of ischemia. The glutamate transporter EAAT2 and the metabolite taurine were found to be key histopathological markers of affected parenchymata. In conclusion, a differential metabolite profile can be detected according to the severity of hydrocephalus and associated ICP and therefore can be used to monitor the efficacy of experimental therapies.
Keywords: Hidrocefalia; Líquido cefalorraquídeo; Hydrocephalus; Metabolite; hyh